Circadian rhythms, jet lag, and shift work, with particular reference to athletes - Waterhouse, J.; Edwards, B.; Carvalho-Bos, S.; Buckley, P.; Reilly, T. (European Journal of Sport Science, 2002)
Changes in individuals' sleep-wake cycles lead to negative side effects. This review considers how side effects can be reduced, the recommendations being based largely on work performed at our institute. Subjects journeying to Australia had symptoms of jet lag that did not adjust synchronously, and the best predictors of jet lag were their travel arrangements. The value of melatonin in reducing jet lag was not confirmed but, in a laboratory-based study, evening administration of melatonin did not result in worse performance the next morning. The effects of exercise upon the phase of the body clock were insubstantial. Gut temperature, unlike insulated axilla temperature, was an acceptable substitute for rectal temperature. Ascertaining by questionnaire why people ate or did not eat at a particular time indicated that night work exerted a considerable disruptive influence, one of the main factors being time pressure. Compared with day workers, night workers had less appetite, ate cold rather than hot meals, and felt more bloated after a meal. Actimetry provided objective measures of the adjustment of the sleep-wake cycle to time-zone transitions and to night work. These measures could be applied to data from long-haul pilots, in whom there are both time-zone transitions and night work.